PENGARUH PLATFORM RUANG MURID TERHADAP HASIL BELAJAR SISWA KELAS IV PADA MATA PELAJARAN IPAS MATERI KENEKARAGAMAN HAYATI - Widad, Helga Merilla Zafirah; Prasetya, Agung Tri; Muh. Sholeh; Kurniawan, Edi; Armaidi, Indriana Eko; Raharjo, Tri Joko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of using the Ruang Murid Platform on the learning outcomes of fourth-grade elementary school students in biodiversity topics. The study was motivated by low student achievement and the underutilization of digital learning facilities in the classroom. The research employed a quasi-experimental method with a nonequivalent control group design involving 38 students, consisting of an experimental group and a control group. The experimental group used the Ruang Murid Platform supported by an Interactive Flat Panel (IFP), while the control group used conventional learning media. The results showed that the experimental group achieved significantly higher posttest scores compared to the control group. Statistical analysis also indicated a significant difference between the two groups (p-value < 0.05). These findings indicate that the use of the Ruang Murid Platform can effectively improve student learning outcomes, particularly when supported by interactive media such as IFP. This study also highlights the potential of digital learning platforms in supporting technology-based learning in elementary education.